Optimization of Trio-Cavity Raman Laser Pumped by Pulsed Gaussian Beam - Khoa, Dinh Xuan; Lanh, Chu Van (Communications in Physics, 2013)
In the paper the set of dimensionless rate equations for the pump, Stokes and anti-Stokes powers in the trio-cavity Raman laser pumped by pulsed Gaussian beam is introduced. By numerical Runger-Kuta method, those equations are resolved and the optimal normalized parameters for enhance the output powers are found out.